Critical Role of Structural Water for Enhanced Li+ Insertion Kinetics in Crystalline Tungsten Oxides. Issue 3 (1st March 2022) - Mitchell, James B.; Wang, Ruocun; Ko, Jesse S.; Long, Jeffrey W.; Augustyn, Veronica
Abstract : Electrochemical ion insertion into transition metal oxides forms the foundation of several energy technologies. Transition metal oxides can exhibit sluggish ion transport and/or phase-transformation kinetics during ion insertion that can limit their performance at high rates (<10 min). In this study, we investigate the role of structural water in transition metal oxides during Li + insertion using staircase potentiostatic electrochemical impedance spectroscopy (SPEIS) and electrochemical quartz crystal microbalance (EQCM) analysis of WO3 ·H2 O and WO3 thin-film electrodes. Overall, the presence of structural water in WO3 ·H2 O improves Li + insertion kinetics compared to WO3 and leads to a less potential-dependent insertion process. Operando electrogravimetry and 3D Bode impedance analyses of nanostructured films reveal that the presence of structural water promotes charge accommodation without significant co-insertion of solvent, leading to our hypothesis that the electrochemically induced structural transitions of WO3 hinder the electrode response at faster timescales (<10 min). Designing layered materials with confined fluids that exhibit less structural transitions may lead to more versatile ion-insertion hosts for next-generation electrochemical technologies.